Educational Technology and the Changing Shape of Education: A Roadmap to 21st Century Learning - Diyal, Suresh Bahadur; Pandey, Romkant (Innovative Research Journal, 2025)
This paper investigates how digital technologies, including online platforms, artificial intelligence, mobile applications, and immersive tools such as virtual and augmented reality, are transforming the landscape of education. Drawing from global experiences and theoretical perspectives, the study explores how EdTech promotes personalized learning, enhances accessibility, and supports competency-based education aligned with 21st-century skills. Educational technology (EdTech) has become a cornerstone of modern education, reshaping how teaching, learning, and assessment are conducted. A systematic review of literature from 2015 to 2024 was conducted using databases including Scopus, Web of Science, and IEEE Xplore to examine opportunities and risks associated with EdTech integration. Findings reveal that while advanced economies are moving toward hybrid and AI-driven learning ecosystems, developing countries continue to face persistent inequalities in digital adoption. The paper also identifies challenges such as the digital divide, inadequate infrastructure, teacher readiness, and ethical concerns related to data privacy and algorithmic bias. The study argues that technology alone cannot transform education; rather, it must be strategically integrated into pedagogy, curriculum, and assessment through well-designed policies and teacher professional development. The paper concludes with a proposed roadmap for equitable, innovative, and sustainable technology integration in education, with implications for both global and local contexts.